The effect of adding active flexion to modified Kleinert regime on outcomes for zone 1 to 3 flexor tendon repairs. A prospective randomized trial. (November 2017) - Rigó, István Zoltán; Haugstvedt, Jan-Ragnar; Røkkum, Magne
In a prospective randomized study, we studied whether adding active flexion to a modified Kleinert regime changed outcomes of flexor tendon repairs in zone 1, 2 and 3 in 73 fingers (53 patients). Evaluation included active range of finger motion, grip and pinch strengths. Twelve months after surgery, the increase in range of active finger motion after adding active flexion was insignificant compared with that with the modified Kleinert regime. According to the Strickland criteria, 20 out of 29 fingers had excellent or good recovery after adding active flexion, as did 28 out of 34 fingers with the modified Kleinert regime; we could not detect significant improvement of the good and excellent rate. At 6 months, the pinch strength was significantly higher with the addition of active flexion. We failed to find that adding active finger flexion to the modified Kleinert regime improves the overall long-term results of repairs in zone 1 to 3, though recovery appeared faster, and the good and excellent recovery of zone 2 repairs was 17% greater with the active flexion protocol. : Level of evidence: I